Effect of Lantana camara Linn. on Biomass Production and Carrying Capacity of forest Areas of Shiwalik Hills of Punjab - Luna, R. K.; Manhas, R. K.; Banyal, S.; Kamboj, S. K. (Indian Forester, 2009)
Experiments were conducted to control Lantana camara in Shiwalik hills of Punjab through chemical treatment (Glyphostate 1.0% spray at stump level) and by planting four fastgrowing species viz.Dendrocalamus strictus, Leucaena leucocephala, Albizia procera (White siris) and Melia azedarach (Drek) after stubbing Lantana at Patahankot, Hoshiarpur and Ropar. Under these five treatments effect of Lantana on biomass production of palatable and non-palatable species and carrying capacity of sites was studied. Biomass studies show that contribution of non-palatable species in control and chemical treatments was very high ranging between 71.80% to 98.84%. Total biomass of palatable and non-palatable species was also found to be very high in all the control treatments mainly due to the dominance of L. Camara. However, dominance of L. camara was found to be low in Bamboo, Leucaena, Whitesiris and Drek treatments. Though L. camara was negatively correlated with H' (Shannon- Wiener's Index) of non-palatable species, it significantly affected H' of palatable species under four treatments of fast-growing species except bamboo treatment. Cd (Simpson's Index) was observed inversely related to H' in all treatments. Correlation analysis showed significant relationship between biomass and H', which meant that with the increase of diversity, biomass of palatable species also increased significantly. The values of carrying capacity showed that the chemical and control treatments had 'very poor' (<1.07 cows ha-1) and other treatments had 'poor' (<3.89 cows ha-1) carrying capacity. The study suggests that plantations of fast growing species hinder the growth of Lantana camara and help to increase the biomass of palatable species thereby upgrading the carrying capacity of the forests though marginally within a short period 2-3 years.